Helicobacter pylori and its association with autoimmune diseases: systemic lupus erythematosus, rheumatoid arthritis and Sjögren syndrome - Ivet Etchegaray-Morales (Elsevier, 2021)
Helicobacter pylori (H. pylori) is a gram-negative bacterium that adapts to the gastric mucosa and provokes symptoms associated with gastritis. Chronic H. pylori infection in patients with a genetic predisposition can trigger autoimmune diseases due to the immune interaction of cellular and humoral responses. Infections are a triggering factor for systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), and Sjögren syndrome (SS), although the association between H. pylori and these diseases is unclear. Therefore, we reviewed this interaction and its clinical importance.